2a. (a, b and c are all equal.)
2a + 2b = 160 But b = a + 40 so 2a + 2(a + 40) = 160 ie 2a + 2a + 80 = 160 or 4a = 80 ie a = 20 Then b = a + 40 gives b = 20 + 40 = 60 Solution: a = 20, b = 60
2a + 2b = c subtract 2a from both sides 2a - 2a + 2b = c - 2a 2b = c - 2a divide both sides by 2 (2/2)b = (c - 2a)/2 b = (c - 2a)/2 --------------------
Let's solve this equation together, friend. To isolate b, we can start by subtracting 2a from both sides of the equation. This will leave us with b equals P minus 2a. Remember, there are many ways to approach a problem, and it's all about finding the one that works best for you.
:a = .5(hb+c) :2a = hb+c :2a−c = hb :(2a−c)/h = b
a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)
2a. (a, b and c are all equal.)
2a + 2b = 160 But b = a + 40 so 2a + 2(a + 40) = 160 ie 2a + 2a + 80 = 160 or 4a = 80 ie a = 20 Then b = a + 40 gives b = 20 + 40 = 60 Solution: a = 20, b = 60
2a + 2b = c subtract 2a from both sides 2a - 2a + 2b = c - 2a 2b = c - 2a divide both sides by 2 (2/2)b = (c - 2a)/2 b = (c - 2a)/2 --------------------
Let's solve this equation together, friend. To isolate b, we can start by subtracting 2a from both sides of the equation. This will leave us with b equals P minus 2a. Remember, there are many ways to approach a problem, and it's all about finding the one that works best for you.
37
:a = .5(hb+c) :2a = hb+c :2a−c = hb :(2a−c)/h = b
b = 2a + 11a + b = 5 which is b = 5 - atherefore2a + 11 = 5 - a (which is b = b)2a + a = - 11 + 53a = - 6a = - 2looking at first equation substitute - 2 for a:b = 2a + 11b = 2*(- 2) + 11b = - 4 +11b = 7to check:a + b = 5- 2 + 7 = 5
A+c= 2a+b
A = h/2*(a + b) So 2A/h = a + b and therefore, a = 2A/h - b
With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)
If ba = 2a + b , then find 23 + 32 +1